2x^2+4x+xy+2y x^2+xy-7x-7y ac+bc+a+b 7z^2-7yz-4z+4y x^3+3x^2+3x+9 pq-p^2-5(p-q) phân tích các đa thức thành nhân tử y^2+1+2y-49 36a^2-c^-9b^2-6bc ab(a

Question

2x^2+4x+xy+2y
x^2+xy-7x-7y
ac+bc+a+b
7z^2-7yz-4z+4y
x^3+3x^2+3x+9
pq-p^2-5(p-q)
phân tích các đa thức thành nhân tử y^2+1+2y-49
36a^2-c^-9b^2-6bc
ab(a-b)+b^2c-bc^2+c^2a-ca^2

in progress 0
Serenity 3 tuần 2021-07-08T17:20:31+00:00 2 Answers 3 views 0

Answers ( )

    0
    2021-07-08T17:21:49+00:00

    `1)2x²+4x+xy+2y`

    `=(2x²+4x)+(xy+2y)`

    `=2x(x+2)+y(x+2)`

    `=(x+2)(2x+y)`

    `2)x²+xy-7x-7y`

    `=(x²+xy)-(7x+7y)`

    `=x(x+y)-7(x+y)`

    `=(x+y)(x-7)`

    `3)ac+bc+a+b`

    `=(ac+bc)+(a+b)`

    `=c(a+b)+(a+b)`

    `=(a+b)(c+1)`

    `4)7z²-7yz-4z+4y`

    `=(7z²-7yz)-(4z-4y)`

    `=7z(z-y)-4(z-y)`

    `=(z-y)(7z-4)`

    `5)x³+3x²+3x+9`

    `=(x³+3x²)+(3x+9)`

    `=x²(x+3)+3(x+3)`

    `=(x+3)(x²+3)`

    `6)pq-p²-5(p-q)`

    `=(pq-p²)-5(p-q)`

    `=p(q-p)+5(q-p)`

    `=(q-p)(p+5)`

    `7)y²+1+2y-49`

    `=(y²+2y+1)-49`

    `=(y+1)²-7²`

    `=(y+1+7)(y+1-7)`

    `=(y+8)(y-6)`

    `8)36a²-c²-9b²-6bc`

    `=(6a)²-(9b²+6bc+c²)`

    `=(6a)²-[(3b)²+2.3b.c+c²]`

    `=(6a)²-(3b+c)²`

    `=(6a-3b-c)(6a-3b+c)`

    `9)ab(a-b)+b²c-bc²+c²a-ca²`

    `=a²b-ab²+b²c-bc²+c²a-ca²`

    `=(c²a-bc²)+(b²c-ca²)+(a²b-ab²)`

    `=c²(a-b)+c(b²-a²)+ab(a-b)`

    `=c²(a-b)-c(a²-b²)+ab(a-b)`

    `=c²(a-b)-c(a+b)(a-b)+ab(a-b)`

    `=(a-b)[c²-c(a+b)+ab]`

    `=(a-b)(c²-ac-bc+ab)`

    `=(a-b)[(c²-bc)-(ac-ab)]`

    `=(a-b)[c(c-b)-a(c-b)]`

    `=(a-b)(c-b)(c-a)`

    0
    2021-07-08T17:22:23+00:00

    $(2x^2+4x+xy+2y)$

    =$2x(x+2)+y(x+2)$

    =$(x+2)(2x+y)$

    $(x^2+xy-7x-7y)$

    =$x(x+y)-7(x+y)$

    =$(x+y)(x-7)$

    $(ac+bc+a+b)$

    =$c(a+b)+(a+b)$

    =$(a+b)(c+1)$

    $(7z^2-7yz-4z+4y)$

    =$7z(z-y)-4(z-y)$

     =$(z-y)(7z-4)$

    $(x^3+3x^2+3x+9)$

    =$x^2(x+3)+3(x+3)$

    =$(x+3)(x^2+3)$

    $(pq-p^2-5(p-q))$

    =$p(q-p)+5(q-p)$

    =$(q-p)(p+5)$

    $(y^2+1+2y-49)$

    =$(y^2+2y+1)-49$

    =$(y+1)^2-7^2$

    =$(y+1-7)(y+1+7)$

    =$(y-6)(y+8)$

    $(36a^2-c^2-9b^2-6bc)$

    =$[(6a)^2-(c^2+6bc+9b^2)$

    =$[(6a)^2-(c+3b)^2]$

    =$(6a-3b-c)(6a+3b+c)$

    $(ab(a-b)+b^2c-bc^2+c^2a-ca^2($

    =$a^2b-ab^2+b^2c-bc^2+c^2a-ca^2$

    =$(a^2b-bc^2)+(-ab^2+b^2c)+(c^2a-ca^2)$

    =$b(a^2-c^2)-b^2(a-c)-ca(a-c)$

    =$b(a-c)(a+c)-b^2(a-c)-ca(a-c)$

    =$(a-c)(ab+bc-b^2-ca)$

    =$(a-c)[(ab-b^2)+(bc-ca)]$

    =$(a-c)[b(a-b)-c(a-b)]$

    =$(a-b)(b-c)(a-c)$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )